Manoeuvring between interplay and context- an ethnographic study of social interaction in encounters between registered nurses, older patients and their relatives - Anette Johnsson; Åse Boman; Petra Wagman; Sandra Pennbrant (BMC, 2021)
Abstract Background Social interactions between registered nurses, older patients and their relatives are essential and play a central role in developing a successful care relationship in healthcare encounters. How nurses interact with patients affects the patient's well-being. Limited time and demands for efficiency influence the encounter and complaints from patients and relatives often concern social interactions. Therefore, the aim of this study was to explore the social interaction in encounters between registered nurses, older patients and their relatives at a department of medicine for older people. Methods The study has an ethnographic approach including participatory observations (n = 21) and informal field conversations (n = 63), followed by a thematic analysis with an abductive approach reflecting Goffman's interactional perspective. Result The result revealed a pattern where the participants manoeuvred between interplay and context. By manoeuvring, they defined roles but also created a common social situation. Nurses led the conversation; patients followed and described their health problems, while relatives captured the moment to receive and provide information. Finally, nurses summarised the encounter using ritual language, patients expressed gratitude through verbal and non-verbal expressions, while relatives verbally confirmed the agreements. Conclusion The social interaction between registered nurses, older patients and relatives was shaped by a pattern where the participants manoeuvred between interplay and context. When all participants assume responsibility for the social interaction, they become active and listen to each other. The approach adopted by nurses is crucial, thus training in communication and social interaction skills are important. When the asymmetry due to imbalance, is reduced, less misunderstanding and a satisfactory care relationship can be achieved.